2001
DOI: 10.1046/j.1460-9568.2001.01372.x
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte-endothelial cell calcium signals conveyed by two signalling pathways

Abstract: Astrocytes and endothelial cells are in close contact with each other at the blood-brain barrier, where important molecular transports take place. Despite these key morphological and functional properties, little is known regarding the dynamic signalling processes that occur between these two cell types. We investigated astrocyte-endothelial cell calcium signalling mechanisms in a coculture model prepared from primary rat cortical astrocytes and ECV304 cells. We used flash photolysis of caged inositol-trisphos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 64 publications
(84 reference statements)
1
49
0
Order By: Relevance
“…For example, there is growing evidence that in the brain, vascular endothelial cells actively participate in communication of calcium signals or calcium signal propagation, a feature that until recently was attributed only to glial cells, neurons, or astrocytes (57). Astrocyte-endothelial cell cocultures demonstrated that calcium signals could be communicated bidirectionally utilizing both gap junctions and ATPmediated paracrine signaling through purinergic receptors (58,59). The components of both these signaling pathways are present in the ␤-cells and intra-islet endothelial cells (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…For example, there is growing evidence that in the brain, vascular endothelial cells actively participate in communication of calcium signals or calcium signal propagation, a feature that until recently was attributed only to glial cells, neurons, or astrocytes (57). Astrocyte-endothelial cell cocultures demonstrated that calcium signals could be communicated bidirectionally utilizing both gap junctions and ATPmediated paracrine signaling through purinergic receptors (58,59). The components of both these signaling pathways are present in the ␤-cells and intra-islet endothelial cells (60,61).…”
Section: Discussionmentioning
confidence: 99%
“…This would not invalidate the central hypothesis since the NMDA-R could exist within the membranes of the astrocytic processes 24,25 or, perhaps, on the autonomic nerve terminals 3,26 adjacent to the brain capillary barrier. Such NMDA-R could be involved in a Ca 2+ signalling cascade capable of activating glucose transporter (GLUT-1) 27 and/or producing CO 28 in brain endothelial cells. Thus NMDA-R and the associated Ca 2+ signalling in brain capillary system may be instrumental in the coupling of neuronal activity to the extraction of glucose from the blood stream.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent in vivo studies have indicated that cerebral microvessels can survive and maintain barrier integrity in areas of the brain that have experienced extensive astrocyte loss (Krum et al, 1997), although these results are in conflict with a more recent study that showed loss and restoration of barrier integrity in vivo following a temporary focal loss of astrocytes (Willis et al, 2004). It has also been speculated that astrocytes may act as intermediaries to or in conjunction with neurons in the moment-to-moment regulation of cerebral microvascular permeability (Ballabh et al, 2004), in particular via dynamic Ca 2ϩ signaling between astrocytes and the endothelium via gap junctions and purinergic transmission (Braet et al, 2001;Zonta et al, 2003).…”
Section: A Astrocytesmentioning
confidence: 93%